Sketch of Dynamics of Political Islam in Indonesia: Pre-Independence to Indonesian Independence - Rahmatullah Rahmatullah (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2019)
Sketch of Dynamics of Political Islam in Indonesia: Pre-Independence to Indonesian Independence